Hypoglossal Nerve Abnormalities as Biomarkers for Central Nervous System Defects in Mouse Lines Producing Embryonically Lethal Offspring - Lukas F. Reissig; Atieh Seyedian Moghaddam; Fabrice Prin; Robert Wilson; Antonella Galli; Catherine Tudor; Jaqueline K. White; Stefan H. Geyer; Timothy J. Mohun; Wolfgang J. Weninger (Frontiers Media S.A., 2021)
An essential step in researching human central nervous system (CNS) disorders is the search for appropriate mouse models that can be used to investigate both genetic and environmental factors underlying the etiology of such conditions. Identification of murine models relies upon detailed pre- and post-natal phenotyping since profound defects are not only the result of gross malformations but can be the result of small or subtle morphological abnormalities. The difficulties in identifying such defects are compounded by the finding that many mouse lines show quite a variable penetrance of phenotypes. As a result, without analysis of large numbers, such phenotypes are easily missed. Indeed for null mutations, around one-third have proved to be pre- or perinatally lethal, their analysis resting entirely upon phenotyping of accessible embryonic stages.To simplify the identification of potentially useful mouse mutants, we have conducted three-dimensional phenotype analysis of approximately 500 homozygous null mutant embryos, produced from targeting a variety of mouse genes and harvested at embryonic day 14.5 as part of the "Deciphering the Mechanisms of Developmental Disorders" www.dmdd.org.uk program. We have searched for anatomical features that have the potential to serve as biomarkers for CNS defects in such genetically modified lines. Our analysis identified two promising biomarker candidates. Hypoglossal nerve (HGN) abnormalities (absent, thin, and abnormal topology) and abnormal morphology or topology of head arteries are both frequently associated with the full spectrum of morphological CNS defects, ranging from exencephaly to more subtle defects such as abnormal nerve cell migration. Statistical analysis confirmed that HGN abnormalities (especially those scored absent or thin) indeed showed a significant correlation with CNS defect phenotypes. These results demonstrate that null mutant lines showing HGN abnormalities are also highly likely to produce CNS defects whose identification may be difficult as a result of morphological subtlety or low genetic penetrance.